Foucault's futures : a critique of reproductive reason - Deutscher, Penelope, 1966- (Critical life studies., 2017)
"In Foucault's Futures, Penelope Deutscher reconsiders the role of procreation in Foucault's thought, especially its proximity to risk, mortality, and death. She brings together his work on sexuality and biopolitics to challenge our understanding of the politicization of reproduction. By analyzing Foucault's contribution to the politics of maternity and its influence on the work of thinkers such as Roberto Esposito, Giorgio Agamben, and Judith Butler, Deutscher provides new insights into the conflicted political status of reproductive conduct and what it means for feminism and critical theory."--